DNA Barcoding helping the identification of Brazilian cetaceans - Silva, Vanessa Souza (Universidade do Vale do Rio dos Sinos, 2019)
Cytochrome C Oxidase Subunit I (COI) is the mitochondrial gene recognized as the DNA Barcoding and used to identify different animal species. In the case of cetaceans (porpoises, whales and dolphins), the COI can assist in more accurate identification and/or confirm the morphological identity of specimens found in advanced state of decomposition on the Brazilian coast, without evident external diagnostic characters. This study aimed to test the efficiency of the COI in the specific identification of most of the 47 species of cetaceans off the Brazilian coast and to generate their respective sequences for depositing them in public sequence databases, in order to subsidize new work by researchers from any country. Part of the world. To this end, the COI was amplified to 152 specimens collected by 13 Brazilian institutions and sent for analysis. The comparison between the sequences obtained and those of cetacean species previously deposited in GenBank was made by the Blast tool, which is based on the similarity between the sequences, which was performed on the Barcode Of Life Data System platform. In addition, most samples had a specimen deposited in a scientific collection as witness material, or specimen images, which allowed their a priori morphological identification in cases where morphological identification diverged from molecular identification. As a result, COI sequences were obtained from 33 species, which represent 70% of the 47 cetacean fauna recorded for the Brazilian coast. Of the 152 sequences analyzed, the COI gene was inefficient in identifying only two species: Stenella coeruleoalba and S. clymene due to the absence of the so-called “gap barcode”, i.g., the absence of well-established inter and intraspecific limits. These results suggest that barcode DNA was efficient in identifying the great majority of cetacean specimens (~93%) studied. However, for species of Delphinidae family the identification should be integrated with other methods, such as Cyt b, nuclear DNA and morphological character analysis whenerver possible.
Keywords: Cetáceos; Encalhe; Morfológico; Identificação; Molecular; Cetaceans; Stranding; Morphological; Identification; ACCNPQ::Ciências Biológicas::Biologia Geral